The Effect of Green Innovation in influencing Sustainable Performance: Moderating role of Managerial Environmental Concern - Mohd Haizam Mohd Saudi; Obsatar Sinaga; Gusni Gusni; Zalina Zainudin (International Journal of Supply Chain Management, 2019)
The objective of the current examination lies in identifying the association between green innovation, managerial environmental concerns (henceforth, MEC) and manufacturing industry of Malaysia. In particular, the current study seeks to investigate the role of MEC in moderating the impact of green innovation in driving performance. The uniqueness of the current study held in identifying the moderating effect of MEC on innovation-performance nexus using two forms of green innovation. In addition, the novelty of existing study lies in investigating multiple measures of performance. Hence, instead of evaluating the single measure of firm performance (Tang, et al., 2018), the current study analyzed the impact of MEC in moderating the effect of green product and process innovation on two vital proponents of performance, i.e. economic performance and environmental performance of manufacturing firms in Malaysia. We use PLS-SEM to examine the involvement of green innovation in effecting sustainable performance. The outcomes of the examination confirm that economic performance and environmental performance have positive and significantly influenced by green product innovation and green process innovation. The results further confirm that managerial environmental concern has positively and significantly moderates the relationship of green product innovation and green process innovation with environmental performance however, we do not find any evidence of moderating relationship of managerial environmental concern between green process innovation and economic performance and green product innovation and economic performance in Malaysia manufacturing firms.